Experimental study on geopolymer ferro cement slab using various wire meshes - Sreevidya, V.; Anuradha, R.; Venkatasubramani, R. (Journal of Structural Engineering, 2024)
The purpose of this experimental investigation is to study the flexural behavior of fly ash-based geopolymer ferrocement elements. Ferrocement composite is a rich cement mortar mix. In the present study instead of cement mortar Geopolymer mortar of ratio 1:2.5 is used. The alkaline activators used consist of Sodium hydroxide and sodium silicate. The ratio of alkaline solution to flyash adopted is 0.376, 0.386, 0.396and 0.416. Strength study on Geopolymer mortar was conducted and optimum W/B ratio of 0.416 is selected.The dimension of Ferrocement slab adopted is 1000mm x 1000mm x 30mm. Nine numbers of square slabs were prepared with different meshes such as square woven, square welded and expanded metal mesh. The number of layers in each mesh was varied from single, double and triple layers. The specimens were cured for 28 days by ambient curing. Based on the test results, load vs deflection curves were drawn. The effectiveness of the square woven, square welded and expanded metal mesh was compared.